Cannabidiol Enhances Sunitinib Effect in Human Renal Cell Carcinoma by Inducing Apoptosis and Inhibiting Stat3 Signaling Pathway - Abdul Qadir, Danish Abdus Samad, Zurqa Khalid, Fareha Kashan, Mahayrookh Asif, Fatima Rizvi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Renal cell carcinoma (RCC) is considered to be the most frequent form of kidney cancer affecting both men and women worldwide. Monotherapy is not always effective and often results in resistance. Aim: To evaluate cannabidiol and sunitinib combination in human RCC using 786-O cells as an in vitro model. Study Design: Experimental study Place and duration of study: Dow International Medical College, Karachi from 15th November 2021 to 14th May 2022. Methodology: 786-O cells were culture and treated with sunitinib, cannabidiol and the combination of both and the growth inhibition was evaluated using MTT assay, while cell apoptosis was determine using flowcytometry. qPCR was used to analyze the expression of apoptotic genes and STAT3 in sunitinib and cannabidiol treated cells. Results: Sunitinib, cannabidiol and the combination of both drugs showed a dose dependent inhibition on growth of 786-O cells (p <0.001). The rate of apoptosis was 14.4% and 24.3% when treated with cannabidiol and sunitinib respectively. When the two drugs were combined, apoptosis was significantly increased to 50.3% (p <0.001). qPCR showed that cannabidiol enhanced sunitinib induced apoptosis by downregulating anti-apoptotic gene (Bcl-2) and upregulating pro-apoptotic gene (caspase-3 and -9) (p <0.001). Practical Implication Using single drug for treating RCC is not always effective and often results in resistance. Our study suggests that cannabidiol in combination with sunitinib may be a preferable chemotherapeutic option for treatment of RCC. Conclusion: Cannabidiol enhances sunitinib effect in inhibiting RCC and their combination achieved more strong inhibition than either drug alone. Keywords: Cannabidiol, Renal cell carcinoma, Sunitinib, Apoptosis, STAT3, qPCR